INFLUENCE OF BUSINESS REPUTATION ON THE FINANCIAL POSITION OF TOUR AGENCY - V. R. Shilman (Russian Journal of Economics and Law)
In the article is considered the business reputation of tour agency developing during long-term qualitative and professional work; a firm estimation from the part of it's reliefs, contractors, consumers. The positive estimation promotes the gain of new consumers and increasing in the income.